Going Up? Career Progress of Female General Staff Across New Zealand Universities - Ricketts, Kate Elizabeth (Auckland University of Technology, 2012)
This exploratory study examined career motivation, home and occupational salience and the presence of subjective discrimination across female general staff in New Zealand universities, through the use of a self-administered online questionnaire. In this current economic climate, pressures on universities show every sign of increasing and more information is needed to understand how higher education employees are faring in these uncertain times. This information includes hearing from the rarely researched general staff. Further knowledge about this general staff group, recently termed ‘multi-hybrid professionals’ (Whitchurch, 2004) is essential to provide a richer picture of how these staff traverse the career labyrinth. In this thesis, the researcher examined whether female general staff are seeking career development alongside the multiple roles required of them at home and in the community. Examination of whether the women felt they faced additional barriers when compared to female academic staff or their male general staff colleagues was of specific interest in the higher education sector. Respondents were found to possess high levels of career motivation, occupational, home and community salience. Work-based experiences were enhanced by having one’s skills recognised, a good relationship with management and confidence in one’s abilities. In contrast, a perception of limited career opportunities at the participants’ universities reduced the importance placed on work and increased the level of role-based subjective discrimination perceived by participants when they compared themselves to female academic staff. A surprising forty percent of the sample indicated a plan to leave their university either temporarily or permanently over the next five years. As a result, a number of recommendations were made around addressing the adverse impacts of subjective discrimination and the importance of flexibility around paid work structures. If universities wish to attract and retain top quality general staff, they must be aware of the negative effects posed by perceived discrimination and limited career opportunities. Likewise employee initiatives that go beyond the office location (such as flexi-work arrangements) should be encouraged and promoted as part of the plan to further a career in higher education. The primary intent of this study was to contribute to supplementary research around general staff employees. Previous investigations of higher education staff have tended to focus on academics, which highlighted a need for the voice of general staff to be heard in the research literature.
Keywords: General staff; Career; Allied staff; Professional staff; Administrative staff